High protein structural flexibility of a truncated hemoglobin from an antarctic cold-adapted bacterium - Howes, B.D. (2010)
Fil:Boechi, L. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales; Argentina.